2D photodetectors for quantum computing - Alamputra Bin Kamarudin (Nanyang Technological University, 2023)
In this era of technology, almost every household owns a computation device like a computer and new models and variations are constantly being produced every single year to outdo the performance of the predecessor’s device. And one such device is what we have, the classical computer that most of us own. Despite it being excellent for day-to-day basis there’s always something significantly better that can be improved and researching into it and making use of quantum mechanics lead to the discovery of Quantum Computer, mostly known as the next generation computer that is currently widely being researched on because it can revolutionize the current computer technology that we have today and perform features remarkably better than classical computers. Due to its ability to harness superposition and entangle theorem to tackle problems that are complex for classical computers or even the current up to date super computers to do. Despite being better than classical computers there are many complications in building quantum computers itself due to certain conditions like the qubits that are used require a certain environment so that the quantum states are balanced for computation and you must be able to move around and control the algorithm of qubits that is entangled which is not easy to achieve. There’s a lot of parts and problems to Quantum Computing, however, in this report what I will be focusing on is quantum photonics, which make use of photodetectors for applications like image sensors, spectrometry etc. Then we will dive down towards understanding 2D photodetectors and research on how exfoliation process of dry transferring of 2D materials is being done.